Surgical outcomes of acute type A aortic dissection in septuagenarians and octogenarians. (September 2022) - Nakai, Yosuke; Yamada, Toshiyuki; Ogawa, Shinji; Kamiya, Shinji; Saitoh, Yuhei; Suda, Hisao
Background: We studied surgical outcomes of acute type A aortic dissection and compared early and late outcomes between septuagenarians and octogenarians. Methods: From 2010 to 2019, we evaluated 254 consecutive patients with acute type A aortic dissection. We performed emergent operations within 48 h of symptom onset for 188 patients, including 59 septuagenarians and 32 octogenarians. Results: The overall 30-day mortality rate was 8.5% in septuagenarians and 9.4% in octogenarians ( p  = 1.0). The hospital mortality rate was 10.2% in septuagenarians and 12.5% in octogenarians ( p  = 0.74). Multivariate analysis identified prolonged ventilation (≥ 72 h) as a significant risk factor for hospital mortality. Being an octogenarian was not significantly associated with hospital mortality. The actuarial survival rate at 5 years was 80.1% in septuagenarians and 58.5% in octogenarians (log-rank p  = 0.09). The freedom from aortic event rate at 5 years was 91.0% in septuagenarians and 100% in octogenarians (log-rank p  = 0.23). Conclusion: The two groups showed no significant differences in hospital mortality or morbidity. Our tear-oriented strategies might be appropriate for both septuagenarians and octogenarians. Prolonged ventilation (≥ 72 h) was a significant risk predictor for hospital mortality.